Democratic Elections Legitimacy Criteria and Challenges of Legitimacy - Amal Hndy Alxazali (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The content of democracy implies participation and representation. The description of some procedures as democratic or legitimate or describing a certain style in the administration as democratic means the active participation of the individuals involved in the decision-making process and when describing some political systems as democratic, this means that representatives were elected through voting processes Free to make decisions on behalf of the decision-making on behalf of individuals who are members of such systems, ie individuals do not participate in the decision-making process but representatives are accountable to their constituents.Elections are the mainstay of the democratic system. The process of political elections is based on competition. The elections are conducted on a regular basis. Voters can choose between different candidates in a pluralistic manner. All the adult citizens can participate in the electoral process either as voters or as candidates for positions. Political issues. The problem is whether it starts with the question: If elections are the best way to reach the legitimacy of governments in democratic countries, how can this mechanism become a means of legitimizing governments and authoritarian regimes.